Strategi Manajemen Sumber Daya Manusia Sebagai Peningkatan Daya Saing Perusahaan - Ahmad Salim; Lisnawati Lisnawati (International Forum of Researchers and Lecturers, 2024)
Human resource management (HRM) plays an important role in helping organizations achieve short-term and long-term goals by aligning those goals with overall business strategy. The purpose of writing this paper is to determine the relationship between Human Resource Management (HRM) and business strategy and to provide an overview of effective employee training and development to increase company productivity. The research method used is qualitative with data collection techniques through literature study. Based on the studies conducted, it is known that the assumption of a close relationship between business strategy and HRM methods is based on contingency theory. This theory emphasizes that human resource management methods are selected according to the type of competitive strategy adopted by the business. A well-crafted business strategy should align with the company's core mission and vision, and serve as a roadmap for achieving profitability, competitiveness and sustainable growth. In addition, proper training and development can significantly influence employee productivity, which in turn will improve the well-being and prosperity of the company. This shows the importance of planning and implementing training and workforce development, both at the company and public levels, to achieve the organization's long-term goals. Keywords: , , , ,